Comparison of single versus double intra uterine insemination - Pathak, B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Intrauterine insemination (IUI) is the best studied and most widely practised artificial insemination technique. The aim and objective of this study was to compare the efficacy of single and double intrauterine insemination. Methods: This prospective randomized study was carried out in 197 infertile couples. Controlled ovarian hyperstimulation was carried out by standard ovulation induction protocols. Single intrauterine insemination was applied 36 hours after human chorionic gonadotropin (hCG) injection to 101 patients in the first group. Double intrauterine inseminations were carried out in 96 patients to whom the first insemination was done after 24 hours and the repeat insemination was done after 48 hours of hCG injection. Results: In the single IUI group 14 patients conceived with pregnancy rate of 13.86%. In the double IUI group 18 patients conceived with pregnancy rate of 18.75%. There was no statistically significant difference between the two groups as the p is more than 0.05. Conclusions: As double intrauterine insemination does not give better result and it involves more cost and stress to the couple, single intrauterine insemination should be preferable. However, further larger sample size studies are required for confirmation if any significant difference can be achieved between the two approaches.